Improved cardiac and venous pressures during hospital stay in patients with acute heart failure : an echocardiography and biomarkers study - Akiyama, Eiichi (2020)
© 2020 The Authors. ESC Heart Failure published by John Wiley & Sons Ltd on behalf of the European Society of Cardiology. This is an open access article under the terms of the Creative Commons Attribution-Non Commercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.